Bergenin, Isolated Compound from Crassula ovata Plant, Its Role as Synergistic Effect With Docetaxel Against Prostatic Cancer (PC-3) Cell Lines - Hawraa Kareem Lifta; Kadhim, enas Jawad (Iraqi Journal of Pharmaceutical Sciences, 2025)
The synergistic effect of the bergenin compound, derived from the Crassula ovata plant, and the docetaxel drug in vitro cell line was assessed in this study. The bergenin compound was extracted using a Soxhlet device and 85% ethanol, then was identified and isolated using a high-performance liquid chromatograph. Docetaxel is regarded as a potent chemotherapy treatment that was licensed in 1996 to treat a variety of cancers, including prostate cancer, by preventing microtubular depolymerization and reducing the impact of bcl-2 and bcl-xL gene expression. It is considered one of the most effective chemotherapy treatment for prostatic cancer. However, it has adverse effects, including febrile neutropenia or myelosuppression. This study aim to combine the docetaxel with new natural compound as there is no previous study on combination between the docetaxel and bergenin to reduce the therapeutic dose as much as possible and obtain same therapeutic effect .The results demonstrated that bergenin exhibits a good synergistic effect against prostatic cancer with IC50 equal to 26 as a phenolic compound that can induce G0/G1 cell cycle arrest, enhance the expression of Bax, decrease the expression of Bcl-2, and inhibit the PI3K/AKT/mTOR pathway. As revealed by the results, the inhibition effect of the combination (bergenin and IC50 docetaxel equal to 89,8) was 64, compared to an inhibition effect of 62 for 100 mcg of docetaxel and the data obtained were analyzed by one-way ANOVA with a significance level of "p < 0.05" .